Genotype-Specific Interaction of Latent TGFβ Binding Protein 4 with TGFβ - Lamar, Kay-Marie (PLoS One, 2016)
Latent TGFβ binding proteins are extracellular matrix proteins that bind latent TGFβ to form the large latent complex. Nonsynonymous polymorphisms in LTBP4, a member of the latent TGFβ binding protein gene family, have been linked to several human diseases, underscoring the importance of TGFβ regulation for a range of phenotypes. Because of strong linkage disequilibrium across the LTBP4 gene, humans have two main LTBP4 alleles that differ at four amino acid positions, referred to as IAAM and VTTT for the encoded residues. VTTT is considered the “risk” allele and associates with increased intracellular TGFβ signaling and more deleterious phenotypes in muscular dystrophy and other diseases. We now evaluated LTBP4 nsSNPs in dilated cardiomyopathy, a distinct disorder associated with TGFβ signaling. We stratified based on self-identified ethnicity and found that the LTBP4 VTTT allele is associated with increased risk of dilated cardiomyopathy in European Americans extending the diseases that associate with LTBP4 genotype. However, the association of LTBP4 SNPs with dilated cardiomyopathy was not observed in African Americans. To elucidate the mechanism by which LTBP4 genotype exerts this differential effect, TGFβ’s association with LTBP4 protein was examined. LTBP4 protein with the IAAM residues bound more latent TGFβ compared to the LTBP4 VTTT protein. Together these data provide support that LTBP4 genotype exerts its effect through differential avidity for TGFβ accounting for the differences in TGFβ signaling attributed to these two alleles.